2022
DOI: 10.14334/wartazoa.v32i1.2585
|View full text |Cite
|
Sign up to set email alerts
|

Revisit the Development of Native Indonesian Chickens from Red Jungle Fowls (Gallus gallus bankiva) to Commercial Chickens

Abstract: Kampung chicken which is one of native Indonesian chickens has been domesticated from the ancestor of Red Fowl Jungle, and developed by the village community from generation to generation through an extensive rearing method. Before the intensive management of kampung chicken was introduced, the chickens were allowed to scavange around the household yard during the day, they slept in the trees, on the roofs or underneath of the household at night. It has been for many years that kampung chickens were crossed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Chia and Momoh [8] found that the proportion of white ducks was lower at 30.33%; the rest were black ducks. Tamzil et al [9] found that in female mallard ducks, white feather color was more dominant than white-spotted black feather color with a frequency of 62 and 38%, respectively, while in male ducks, white feather color and whitespotted black feather color had a balanced frequency (50:50).…”
Section: Introductionmentioning
confidence: 99%
“…Chia and Momoh [8] found that the proportion of white ducks was lower at 30.33%; the rest were black ducks. Tamzil et al [9] found that in female mallard ducks, white feather color was more dominant than white-spotted black feather color with a frequency of 62 and 38%, respectively, while in male ducks, white feather color and whitespotted black feather color had a balanced frequency (50:50).…”
Section: Introductionmentioning
confidence: 99%
“…The genetics of the chicken breed strongly influence the immune response of chicken to Salmonella challenges (Kaiser et al 2022). Indonesian local chicken have 32 breeds (Winaya et al 2023) that are the result of the domestication of Red junglefowl and an important asset for the formation of superior breeds because of their ability to adapt well (Tamzil & Indarsih 2022). This study used KUB-1 chicken, which has been designated as a superior strain through the Decree of the Minister of Agriculture of the Republic of Indonesia No.…”
Section: Introductionmentioning
confidence: 99%